Text (Context) Comprehension and Structuring via Different Types of Presuppositions - Tovmasyan, Hranush (Armenian Folia Anglistika, 2012)
The current article highlights the mechanisms of text (context) perception, coherence and construction with the help of various types of presuppositions. The author distinguishes between different presuppositions, such as egotistical, functional, communicative and linguistic, and discusses the contribution of each to the perception, coherence and construction of the text.